The Concept of Assimilation, according to Ibn Jenny, Through the Lexicon of Al-Khasāsīs: Comparative Study - Mardiya Abobaker Elzouki (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2024)
The purpose of this research is to examine Ibn Jinni’s definition of assimilation using the Lexicon of Al-Khasāsīs. It focuses on drawing parallels between the English language and Ibn Jinni’s Lexicon of Al-Khasāsīs. Ibn Jannah said that in his discussion of the phonetic component of the language and how to pronounce it, the study addressed this portion. The Dictionary of Al-Khasāsīs was used in the study to demonstrate how the assimilation processes of the Arabic and English languages differ from one another. Whereas in English, assimilation is represented by consonants, where a sound is assimilated to a neighbouring sound, in Arabic it is expressed by vowels or letter by letter. A phonetic process called assimilation involves blending one sound with its nearby counterpart. Complete, partial, progressive, and regressive assimilation are all included. Nonetheless, the study concluded that assimilation is crucial for improving the ease and speed of word or speech pronunciation. The vocabulary provided by the results further demonstrated how smaller assimilation is facilitated by the deviation process, which is also known as letter approximation.